187k views
1 vote
Given that f(x) = x² + 5x, evaluate f(-2).If g(x)=2x + 1, find g(a + h)- g(a).

User AlexFZ
by
4.8k points

1 Answer

7 votes


\\ \sf\longmapsto f(x)=x^2+5x


\\ \sf\longmapsto f(-2)=(-2)^2+5(-2)


\\ \sf\longmapsto f(-2)=4-10


\\ \sf\longmapsto f(-2)=-6

.#2


\\ \sf\longmapsto g(x)=2x+1


\\ \sf\longmapsto g(a)=2a+1


\\ \sf\longmapsto g(a+h)=2(a+h)+1

.Now


\\ \sf\longmapsto g(a+h)-g(a)


\\ \sf\longmapsto 2(a+h)+1-2a-1


\\ \sf\longmapsto 2a+2h+1-2a-1


\\ \sf\longmapsto 2h

User Soroush Hakami
by
5.1k points